Cell and Developmental Biology of Plant Mitogen-Activated Protein Kinases - Komis, George; Šamajová, Olga; Ovečka, Miroslav; Šamaj, Jozef (Annual review of plant biology, 2018)
Plant mitogen-activated protein kinases (MAPKs) constitute a network of signaling cascades responsible for transducing extracellular stimuli and decoding them to dedicated cellular and developmental responses that shape the plant body. Over the last decade, we have accumulated information about how MAPK modules control the development of reproductive tissues and gametes and the embryogenic and postembryonic development of vegetative organs such as roots, root nodules, shoots, and leaves. Of key importance to understanding how MAPKs participate in developmental and environmental signaling is the characterization of their subcellular localization, their interactions with upstream signal perception mechanisms, and the means by which they target their substrates. In this review, we summarize the roles of MAPK signaling in the regulation of key plant developmental processes, and we survey what is known about the mechanisms guiding the subcellular compartmentalization of MAPK modules.
Keywords: rostliny; Plants; rostlinné buňky; cytoskeleton; vývojová biologie; mitogenem aktivované proteinkinasy; Plant Cells; Developmental Biology; MAP kinasový signální systém; subcellular localization; nucleus; MAP Kinase Signaling System; plant development; mitogen-activated protein kinase; Mitogen-Activated Protein Kinases; Organ Specificity; signaling; orgánová specificita